Identification and characterisation of subtypes of patients in a bipolar cohort - Kwek, Germaine Dan Yi (Nanyang Technological University, 2021)
This research identifies subtypes of bipolar patients using gene expression data and uncovers their underlying biological themes. This sheds some light on the variation within bipolar disorder and contributes to customised treatment of patients. This research has three parts: reducing the dimensionality of the data (F-test and Principal Component Analysis), identification of the subtypes (K-means clustering), and analysing the biological themes underlying the subtypes (Gene Set Enrichment Analysis and Gene Ontology Analysis). The results show that mitochondrial dysregulation, telomere-related processes, and telomerase RNA localisation to Cajal bodies drive the differences between subtypes. Future researchers might want to further investigate each theme.